Tretinoin for Photodamaged Facial Skin: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Huang, Hsin-Yin; Lee, Leon Tsung-Ju (Dermatology Practical & Conceptual, 2025)
Introduction: Randomized controlled trials have suggested that tretinoin, a topical retinoid, can improve wrinkling in photodamaged skin; however, its overall effectiveness remains subject of debate. Objectives: This study evaluated the efficacy and safety of tretinoin in treating facial wrinkles induced by photodamage. Method: We systematically searched the PubMed, EMBASE, and Cochrane CENTRAL databases from their inception to 16 January 2024 to identify randomized controlled trials comparing topical tretinoin with vehicle treatments. Data were synthesized using a random effects model, and sensitivity analyses were performed to evaluate the robustness of the results in the presence of potential bias. Results: This study identified eight trials (1,361 patients; median age range 29–76 years; average follow-up duration, 16 weeks to 2 years) that met the inclusion criteria. Compared with the vehicle, topical tretinoin significantly improved clinical signs of facial photodamage. Improvements were observed in both fine wrinkles (mean difference [MD]: 0.412; 95% confidence interval [CI]: 0.233–0.590; P<0.001) and coarse wrinkles (MD: 0.245; 95% CI: 0.119–0.370; P<0.001). Sensitivity analyses confirmed the robustness of these findings. Conclusion: Topical tretinoin is a safe and effective treatment for fine and coarse facial wrinkles resulting from photodamage.